A Review of Mosquitoes Associated with Rift Valley Fever Virus in Madagascar - Tantely, Luciano M. (Am J Trop Med Hyg, 2015)
Rift Valley fever (RVF) is a viral zoonotic disease occurring throughout Africa, the Arabian Peninsula, and Madagascar. The disease is caused by a Phlebovirus (RVF virus [RVFV]) transmitted to vertebrate hosts through the bite of infected mosquitoes. In Madagascar, the first RVFV circulation was reported in 1979 based on detection in mosquitoes but without epidemic episode. Subsequently, two outbreaks occurred: the first along the east coast and in the central highlands in 1990 and 1991 and the most recent along the northern and eastern coasts and in the central highlands in 2008 and 2009. Despite the presence of 24 mosquitoes species potentially associated with RVFV transmission in Madagascar, little associated entomological information is available. In this review, we list the RVFV vector, Culex antennatus, as well as other taxa as candidate vector species. We discuss risk factors from an entomological perspective for the re-emergence of RVF in Madagascar.